Bloodstrike: battleblood, volume 1 ebook - Liefeld, Rob (Bloodstrike: Battleblood, 2024)
Limited edition oversized hardcover. BLOODSTRIKE is back! A new recruit to the Bloodstrike program is compromised and struggles on a covert mission that puts him on a collision course with his former squadron! Unload the guns and ammo in this action-packed spectacle by ROB LIEFELD (Deadpool, X-Force)! Guest starring Brigade and Bloodwulf!